Visual-motor conflict in cognitive strategies during mental rotation: The role of embodiment and specific sport expertise. - Habacha, Hamdi; Ben Mehrez, Ahmed (Visual Cognition, 2025)
This study investigated how visual features of stimuli influence cognitive strategies during mental rotation. Wrestlers, athletes from other sports, and non-athletes mentally rotated standard objects, anatomically possible-body configurations, and impossible-body configurations. Performance in non-athletes and other athletes declined with impossible configurations, reflecting the disruptive effects of embodied strategies when visual and motor representations conflict. In contrast, possible-body configurations facilitated holistic rotations through visual-motor alignment. Interestingly, wrestlers outperformed both groups and maintained stable performance across all stimuli, suggesting an ability to inhibit counterproductive embodied strategies and adopt more efficient cognitive strategies depending on stimuli affordances. Under movement constraints, mental rotation was disrupted for non-athletes and other athletes, whereas wrestlers remained unaffected, indicating their reliance on more efficient adaptive strategies. These findings highlight the influence of visual features of stimuli in shaping cognitive strategies and emphasize the enhanced adaptability fostered by specific sensorimotor expertise, such as wrestling, in overcoming visual-motor challenges.